2018
DOI: 10.28991/cej-030991
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behaviour of Lightweight Foamed Concrete Beams Reinforced with GFRP Bars

Abstract: Lightweight foamed concrete is a type of concrete characterized by light in self-weight, self-compaction, self-leveling, thermal isolation, and a high ratio of weight to strength. The advantages of GFRP bars include lightweight, high longitudinal tensile strength, non-conductivity, and resistance to corrosion. This study investigated the behavior of LWFC beams reinforced with GFRP bars under flexural loading. A total of four reinforced concrete beams were cast, where it consisted of two LWFC beams and two norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Moreover, lightweight FC strengthened with glass fibre reinforced polymer (GFRP) bars was investigated and associated with normal concrete beams [166]. It was discovered that lightweight FC has a 3.6% increment of load capacity without reinforcement and an 11.54% increase in GFRP than steel reinforcement.…”
Section: Steel and Frp Rfc Jones And Mccarthymentioning
confidence: 99%
“…Moreover, lightweight FC strengthened with glass fibre reinforced polymer (GFRP) bars was investigated and associated with normal concrete beams [166]. It was discovered that lightweight FC has a 3.6% increment of load capacity without reinforcement and an 11.54% increase in GFRP than steel reinforcement.…”
Section: Steel and Frp Rfc Jones And Mccarthymentioning
confidence: 99%
“…An investigation conducted by Abd and Ghalib [7] focused on analyzing four reinforced concrete beams comprising two foamed concrete beams and two normal-weight concrete beams with dimensions of 200 × 250 × 1500 mm. Te density aimed for the lightweight foamed concrete beams was 1800 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…By comparing lightweight foamed concrete reinforced with GFRP bars to normal concrete beams it was found that the increase in the load capacity for lightweight foamed concrete is 3.6% of the load capacity for normal concrete beams. By comparing lightweight foamed concrete beams reinforced with GFRP bars, it was found that the increase in the load capacity for beam reinforced with GFRP is 11.54% of the load capacity for beams reinforced with steel bars [8]. Lee et al (2017) investigated seven beams of lightly foamed mortar and three beams of normal weight concrete as control samples, the experimental results of the flexural behavior of beams and reinforced concrete slabs made of lightweight foamed mortar with a density ranging from 1700-1800 kg/m 3 , show that light foamed mortar beams can withstand ultimate loads about 8 to 34% lower than normal weight reinforced concrete with the same reinforcing configuration [9].…”
Section: Introductionmentioning
confidence: 99%